Model development and numerical analysis of a vertical falling film absorption heat pump. (10th January 2022) - Wu, Zhangxiang; You, Shijun; Jiang, Tingting; Zhang, Huan; Wang, Yaran; Jiang, Yan; Sha, Li; Wei, Shen
Abstract: Traditional gas fired boilers and air-source heat pumps are not efficient for heating when the outdoor temperature is low, while the air-source heat pump is still one of the most promoting measures for building energy-efficient heating. In this study, a novel air-source gas-fired absorption heat pump with vertical falling film exchangers has been proposed for district heating. Compared with conventional gas fired boilers, the proposed system has higher efficiency, since it can absorb heat from the ambient air. A lumped and distributed parameter coupled numerical model is established to analyze its thermodynamic performance, together with a test rig established to validate the numerical model. Experimental results indicated that when the evaporator temperature increased from −10 °C to −5 °C, the coefficient of performance rose from 1.53 to 1.62, and heating capacity improved from 36.88 kW to 45.32 kW. Additionally, the coupled model showed high prediction accuracy, with the maximum error less than 8%. Due to the opposite contributions of the supply water temperature and water flow rate to the coefficient of performance, the genetic algorithm was adopted to identify the optimal solution of a multi-objective optimization procedure. Results displayed that the proposed system was feasible and efficient for heating in cold region under different operating conditions. Graphical abstract: Image 1 Highlights: An air-source gas-fired absorption heat pump with falling film exchanger is studied. A numerical model including lumped and distributed parameter model is established. A test rig is established to examine the system and validate the numerical model. Multi-objective optimization based on genetic algorithm is applied.